2010
DOI: 10.1021/ja1060406
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Enabling Synthetic Diversification of Natural Products: Chemogenetic Generation of Pacidamycin Analogs

Abstract: Introduction of prnA, the halogenase gene from pyrrolnitrin biosynthesis, into Streptomyces coeruleorubidus resulted in efficient in situ chlorination of the uridyl peptide antibotic pacidamycin. The installed chlorine provided a selectably functionalizable handle enabling synthetic modification of the natural product using mild cross-coupling conditions in crude aqueous extracts of the culture broth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
147
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 19 publications
0
147
0
7
Order By: Relevance
“…6 The ability to functionalise tryptophan is attractive as it provides a handle for selectively tuning the properties of the free amino acid or the amino acid as a component of a natural product or a peptide. We have previously demonstrated a new paradigm in natural product analogue generation, Genochemetics, 7 in which gene installation enables the biosynthetic introduction of a chemically orthogonal handle into a natural product, enabling selective synthetic diversification. Specifically, we demonstrated that we could engineer the production of the antibiotic pacidamycin bearing a 7-chlorotryptophan, the halogen handle enabled synthetic diversification through Suzuki-Miyaura cross coupling chemistry to produce a new array of natural product analogues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The ability to functionalise tryptophan is attractive as it provides a handle for selectively tuning the properties of the free amino acid or the amino acid as a component of a natural product or a peptide. We have previously demonstrated a new paradigm in natural product analogue generation, Genochemetics, 7 in which gene installation enables the biosynthetic introduction of a chemically orthogonal handle into a natural product, enabling selective synthetic diversification. Specifically, we demonstrated that we could engineer the production of the antibiotic pacidamycin bearing a 7-chlorotryptophan, the halogen handle enabled synthetic diversification through Suzuki-Miyaura cross coupling chemistry to produce a new array of natural product analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we demonstrated that we could engineer the production of the antibiotic pacidamycin bearing a 7-chlorotryptophan, the halogen handle enabled synthetic diversification through Suzuki-Miyaura cross coupling chemistry to produce a new array of natural product analogues. 7 The requirement for halotryptophans has stimulated many synthetic studies. Since the first chemical synthesis of 7-chlorotryptophan reported by Rydon and Tweddle, 8 despite many advances, the best methods currently available are multi-step, lack generality or require specialised procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the interest of developing the Suzuki-Miyaura reaction in water resides in the potential to generate novel bioactive molecules. 247 These two criteria -the use of chlorinated reagents, the use of water as a solvent -have been targeted in the recent years using various strategies. For instance, the development of phosphine ligands permitting the solubility of the palladium complex in water has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Further optimization indicated that a related ligand, bearing sulfonated m-xylene groups instead of phenyl (TXPTS), allowed for work at a lower temperature (40 • C) while still presenting excellent yields and significantly improved conversions when introducing a phenyl substituent on the 7-position. Alteration of the ligand to sulfonated 2-dicyclohexylphosphino-2'-6'-dimethoxybiphenyl (SSPhos) was necessary to maintain the applicability of the Suzuki-Miyaura reaction on 7-Cl-tryptophans, as beautifully illustrated by derivatization of the natural product chloropacidamycin in mixed aqueous conditions (water/acetonitrile (AcN) 5:1) [96]. The synthesis of 7-vinyltryptophan 29 with potassium vinyltrifluoroborate and PdCl 2 (dppf), starting from 7-iodotryptophan 28 in mixed aqueous conditions ( Figure 6B), broadened the scope of halotryptophan derivatization, along with the derivatization of unprotected bromotryptophan and bromotryptophan-containing dipeptides [97].…”
Section: Access To and Derivatization Of (Pseudo)halogenated Aromaticmentioning
confidence: 99%